Late-onset neonatal sepsis in preterm infants with birth weight under 1.500 g - Stella Marys Rigatti Silva; Giordana de Cássia Pinheiro da Motta; Cristiane Raupp Nunes; Juliana Machado Schardosim; Maria Luzia Chollopetz da Cunha
Objective: the research objective was to characterize preterm infants with birth weight under 1500 g, and to identify the incidence of late-onset neonatal sepsis among this population. Methods: a prospective cohort study with a sample of 30 preterm newborns that weighed under 1500 g and were hospitalized in the NICU of the university hospital. Data were collected from January to December 2013 using a structured instrument. Results: of the 30 neonates included in the study, 14 developed late-onset neonatal sepsis with a prevalence of coagulase-negative staphylococci. Conclusions: the incidence of late-onset neonatal sepsis indicates a vulnerability in preterm infants due to immunological immaturity. These results reveal that knowledge of the profile of newborn infants admitted to the NICU and the risk factors to which they are exposed are central to the planning of nursing care for these patients. Future studies should address strategies for preventing nosocomial infection.